Interactive E-Module Based on Canva to Improve Students’ Negotiation Text Competence - Talitha, Stella; Aam Nurjaman; Sandi Budiana; Vickry Fadillah; Hilman Abdul Aziz; Althaffina Dzakwaniah (International Journal of Education and Teaching Zone, 2025)
This study aims to develop a digital e-module on negotiation texts for tenth-grade students, integrating contextual content and interactive features in alignment with the Kurikulum Merdeka. Employing the ADDIE model Analysis, Design, Development, Implementation, and Evaluation this research addresses students’ low performance in negotiation text writing and the limited use of engaging digital media in Indonesian language instruction. The e-module was designed using Canva for visual layout and Flipbook Maker for interactive delivery, incorporating authentic scenarios, annotated dialogues, and formative assessments. A mixed-methods approach was adopted, involving expert validation (media, language, and content), student and teacher questionnaires, interviews, observations, and pretest-posttest analysis. Thirty-eight students and two teachers from a public senior high school in Bogor participated in the implementation phase. Validation scores showed high feasibility (media: 90%, language: 100%, content: 96%), while student responses yielded a 92.21% effectiveness rating. Pretest and posttest results showed a substantial learning gain (N-Gain = 0.71), confirming the module’s effectiveness in enhancing students’ comprehension and writing of negotiation texts. The findings suggest that contextually responsive and visually engaging e-modules can significantly improve language learning outcomes. This research contributes to instructional material innovation by offering a feasible and adaptable digital solution for genre-based learning in Indonesian classrooms.